2019
DOI: 10.1007/978-3-030-29736-7_23
|View full text |Cite
|
Sign up to set email alerts
|

A Supervised Learning Model for the Automatic Assessment of Language Levels Based on Learner Errors

Abstract: This paper focuses on the use of technology in language learning. Language training requires the need to group learners homogeneously and to provide them with instant feedback on their productions such as errors [8, 15, 17] or proficiency levels. A possible approach is to assess writings from students and assign them with a level. This paper analyses the possibility of automatically predicting Common European Framework of Reference (CEFR) language levels on the basis of manually annotated errors in a written l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…We envisage various strategies for automatically assessing ESL learners' written proficiency. Firstly, the use of error-rate as a feature may give rather significant results both if used as the only feature, as illustrated by Ballier et al (2019), or if used in combination with other linguistic features, as shown in Yannakoudakis et al (2011), but unlike such studies -in which shallow learning algorithms were employed -we propose to investigate the application of deep neural networks. Secondly, the use of two input texts -one containing answers with errors, the other one containing the corrected versions of the answers -may also result in an efficient approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We envisage various strategies for automatically assessing ESL learners' written proficiency. Firstly, the use of error-rate as a feature may give rather significant results both if used as the only feature, as illustrated by Ballier et al (2019), or if used in combination with other linguistic features, as shown in Yannakoudakis et al (2011), but unlike such studies -in which shallow learning algorithms were employed -we propose to investigate the application of deep neural networks. Secondly, the use of two input texts -one containing answers with errors, the other one containing the corrected versions of the answers -may also result in an efficient approach.…”
Section: Discussionmentioning
confidence: 99%
“…This work was reproduced by Caines and Buttery (2020) who applied such experiments also to English and Spanish corpora. Recently, the work described by Ballier et al (2019) has investigated the possibility of predicting CEFR proficiency levels based on manually annotated errors in the EF-Cambridge Open Language Database (EFCAMDAT) corpus. Their classifier based on a random forest model achieved 70% accuracy.…”
Section: State Of the Artmentioning
confidence: 99%
“…Recently, the work described by Ballier et al (2019) has investigated the possibility of predicting CEFR proficiency levels based on manually annotated errors in the French and Spanish section of the EFCAMDAT corpus, but their study did not employ deep learning techniques. However, they identified that certain types of errors, such as punctuation, spelling and verb tense errors, are characteristic of specific CEFR proficiency levels.…”
Section: Reference To Prior Workmentioning
confidence: 99%
“…Errors, or negative properties of interlanguage, were also tested. Ballier et al, (2019) showed that error-tag frequencies could be used as potential proficiency predictors.…”
Section: Theoretical Background 21 a Multidimensional Set Of 'Criterial Features'mentioning
confidence: 99%
“…Ballier et al . (2019) showed that error-tag frequencies could be used as potential proficiency predictors.…”
Section: Theoretical Backgroundmentioning
confidence: 99%